Prenatal diagnosis of hypomethylation at KvDMR1 and Beckwith-Wiedemann syndrome in a pregnancy conceived by intracytoplasmic sperm injection and in vitro fertilization and embryo transfer - Chih-Ping Chen; Yi-Ning Su; Shee-Uan Chen; Tung-Yao Chang; Pei-Chen Wu; Schu-Rern Chern; Peih-Shan Wu; Yu-Ling Kuo; Wayseen Wang (Elsevier, 2014)
Objective: We report prenatal diagnosis of hypomethylation at KvDMR1 and Beckwith-Wiedemann syndrome (BWS) in a pregnancy conceived by intracytoplasmic sperm injection and in vitro fertilization and embryo transfer. Case report: A 34-year-old, primigravid woman was referred to the hospital at 21 weeks' gestation because of advanced maternal age and an isolated omphalocele in the fetus. Her husband had the fertility problem of oligospermia. This pregnancy was achieved by intracytoplasmic sperm injection and in vitro fertilization and embryo transfer. Prenatal ultrasound revealed a 2.1 cm × 1.6 cm isolated omphalocele. The woman underwent amniocentesis. Array comparative genomic hybridization and methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) were applied to the DNA extracted from the uncultured amniocytes. Conventional cytogenetic analysis and high-resolution melting analysis were performed on cultured amniocytes. Array comparative genomic hybridization revealed no genomic imbalance. MS-MLPA analysis revealed H19DMR(IC1) normal methylation and KvDMR1(IC2) hypomethylation. Conventional cytogenetic analysis revealed a karyotype of 46,XX. High-resolution melting analysis using a methylation-specific polymerase chain reaction assay confirmed normal methylation at H19DMR(IC1) and hypomethylation at KvDMR1(IC2). The altered methylation status at 11p15.5 and the phenotype of omphalocele were consistent with the diagnosis of BWS. Conclusion: In case of prenatally detected omphalocele associated with an obstetric history of assisted reproductive technology, a differential diagnosis of BWS should be considered. Methylation assays such as MS-MLPA and methylation-specific polymerase chain reaction using uncultured amniocytes are useful for rapid diagnosis of BWS under such circumstances.